Decentralization as an Effort to Bring Public Services Closer to the Community: A Literature Review on Its Effectiveness - Arrazak, Muhammad Afdhal; Frinaldi, Aldri; Magriasti, Lince; Naldi, Hendra (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to understand the extent to which decentralization can bring government services closer to the public through the authority granted to regions. This study uses a literature review method by reviewing various scientific articles discussing decentralization and local government practices. The analysis shows that authority at the regional level provides opportunities for services to be more accessible because decisions can be made more quickly, flexibly, and more appropriately to regional conditions. Its effectiveness is evident through various adjustments made by regional governments, ranging from improving governance, restructuring administrative procedures, to managing resources that support service delivery. However, this success is still influenced by the readiness of regions to manage their authority and their ability to directly understand community needs. Overall, decentralization provides a strong foundation for creating closer and more relevant services for citizens when regional governments are able to optimally utilize the spatial authority granted.